Development of novel pyrrolo-1,5-benzoxazepines as anti-cancer agents for the treatment of chronic myeloid leukaemia - Bright, Sandra A. (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2010)
Chronic myeloid leukaemia (CML) is characterised by the presence of a constitutively active tyrosine kinase known as Bcr-Abl. The Bcr-Abl kinase inhibitor, STI571, is the first line treatment for CML, but the recent emergence of STI571 resistance has led to the search for alternative drug treatments and the examination of combination therapies for CML. The recently developed novel set of compounds, the pyrrolo-1,5- baizoxazepines, (PBOXs), can be subdivided into two groups with distinct mechanisms of action, G1 -arresting agents and apoptosis-inducing compounds. In this report, we sought to analyse the effect of various representative PBOX compounds alone and in combination with anti-cancer agents on CML cells.
Keywords: Biochemstry, Ph.D.; Ph.D. Trinity College Dublin.